An incentive scheme in wireless access networks through a game based on trust prediction. (1st October 2012) - Gui, Jinsong; Chen, Zhigang; Deng, Xiaoheng
We propose a game scheme to stimulate cooperation in wireless access networks. Through game analysis, we get an acceptance probability and access control condition. Upon receiving a request from a mobile node, if an access point decides to deal with it based on the acceptance probability, its future trust is predicted. By using the predicted value, access control condition, and mobile node's cheat probability, the access point gets a decision–making result, which decides whether to respond the mobile node's request. We show that our scheme has more favourable incentive effect and less game cost than those of the existing works.